Capital maintenance study, the case of water supply systems in selected small towns - Joseph K. Asante; Kwabena B. Nyarko; Bismark Dwumfour-Asare (2013)
This Capital Maintenance Expenditure (CapManEx) study of seven Small Towns’ Water Systems provides understanding of the recurrent cost elements needed for sustainable services delivery. Field visits were carried out to the water systems and copies of available records on O&M were obtained. A data classification guide was used to classify the data and adjusted to the year 2011 using Gross Domestic Product deflators. The classified data was annualised to find the average total cumulative cost.